Economic benefits of livestock management in Ghana - Adams, Faizal; Ohene-Yankyera, Kwasi; Aidoo, Robert; Wongnaa, Camillus Abawiera (Springer, 2021)
The traditional system of producing small ruminants (sheep and goats) contributes significantly to the socioeconomic wellbeing of farm households in northern Ghana. Besides serving as an important source of income, sheep and goats also offer important non-pecuniary benefits such as the provision of manure, savings, insurance, farm portfolio diversification, and strong social relations. However, technical evaluation of traditional small ruminant systems places much emphasis on financial gains to farmers and abstracts on the non-conventional utilities derived from the livestock system. The main purpose of this study, therefore, is to estimate the overall economic benefits associated with traditional small ruminant systems by accounting for both market and non-market values in two agro-ecological zones (Guinea and Sudan savannah) of northern Ghana. Using a multistage sampling technique, we collected cross-sectional data from 249 small ruminant farmers for empirical analysis. The results show that at least 60% of the net benefits from sheep and goat production in northern Ghana are in non-marketable (non-cash) forms. The study demonstrates that the traditional free-range system of managing sheep and goats is economically viable when the non-market value derived from the system is incorporated in the economic analysis. The findings have practical implications in improving the traditional small ruminant system for higher meat productivity and income generation in northern Ghana and elsewhere in sub-Saharan Africa (SSA).